Active power factor correction using boost converter - jehad, Omar; AbuMassoud, Adnan; radwan, Ala'a (My University, 2018)
In the present situation, the evolution of growing in computers, laptops, uninterrupted power supplies, telecom and biomedical equipment has become overpowering. Hence, the utilization of such equipment results high power consumption and small power density which provided a large market to Distributed Power System (DPS). Power conditioning; typically, rectification is essential usually for electronics equipment. Rectifier behaves as nonlinear load producing non-sinusoidal line current due to the nonlinear input characteristic. The steady growth of use of electronics equipment is become a significant problem as per the line current harmonic is concerned. Their adversative effects on the power system are acknowledged healthy. Hence fore, in three-phase systems, the neutral current magnitude increase and becomes the cause of overheating of transformers and induction motors, as well as the dreadful conditions of system voltage wave forms. There are numbers of international standards to limit the harmonic content, caused due to the line currents of equipment coupled to electricity distribution networks. Accordingly, a reduction in line current harmonics, or Power Factor Correction – PFC is vital. This idea is the inspiration to this research effort. The objective is to improve the power factor nearly unity with minimum Total Harmonic Distortion (THD).